Legal Analysis in Airlines Business Over Middle of Covid-19 Pandemic at Indonesia - Muhammad Nursultan Rachmat; Wasis Susetio (Journal of Multidisciplinary Academic, 2021)
Aviation is an inseparable part of every country's transportation which has dropped dramatically in the wake of the COVID 19 pandemic. Private airlines in Indonesia can continue to operate during the pandemic with passenger numbers are limited by the government about 40% -70%. As the result, high expenses in the cost and declining revenues. Consequently, in a reduction of employee’s number and a reduction employee’s salaries in the salaries who were still in the private aviation sector. Through PERPU No. 1 of 2020, the government provides financial assistance to help the private companies through Bank Indonesia. However, with the help of this regulation, a legal vacuum is created in its implementation in the aviation world to make facing the pandemic in Indonesia. In this situation, aid funds can be misused and misused. In order to avoid further consequences, regarding to the death of private airlines in Indonesia that affecting to all Indonesians people, it is necessary to bring more government attention as a form of solidarity with others. Stakeholders and Indonesian compatriots through a strategic sector policy and to create its implementation. In this case, the central government and the Directorate General of Civil Aviation can learn from other countries by proposing policies such as injection of funds with emphasis on the requirements of continuity of workers' employment contracts, in negotiating payment for aviation fuel, obtaining tax breaks and incentives for lower tariffs for airport services and other policies in the operational sector to encourage the expansion of aviation activities in Indonesia for survive and alive.